Comparison of Maceration and Soxhlet Extraction Methods on Flavonoid Contents from Papaya (Carica papaya) - Windi Anggraini; Mery Napitupulu; Daud K. Walanda; Detris Poba (Jurnal Akademika Kimia, 2025)
The papaya plant offers numerous benefits. Each part of the papaya plant has its benefits, starting from the fruit, stem, roots, flowers, and leaves. Livestock Medicine confirmed the presence of at least 22 types of bioactive compounds. The papaya plant contains active compounds that act as antioxidants, including flavonoids. This research aims to compare maceration and Soxhlet extraction methods on the flavonoid content of papaya (Carica papaya) leaf extract as measured using a UV-Vis spectrophotometer. The methods used to separate flavonoid levels are maceration and Soxhlet extraction. Based on the research that has been carried out, it was found that two treatments were carried out in the maceration method: the first treatment was with 70 % ethanol solvent, namely 36.6 mg / 100g or 3.66 %, for 96 % ethanol solvent, namely 77.6 mg / 100g or 7.76 %. Two treatments are also carried out in the Soxhlet method: 70% ethanol (33.6 mg/100g, 3.36%) and 96% ethanol (92.6 mg/100g, 9.26%). These results indicate that Soxhlet extraction is the most effective method for producing flavonoids in papaya leaf extract, as the levels obtained are higher than those obtained by maceration.